2014
DOI: 10.1007/s00234-014-1437-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and preferential location of intracranial mirror aneurysms: a comparison with non-mirror multiple and single aneurysms

Abstract: Patients with mirror aneurysms had similar clinical characteristics to non-mirror multiple aneurysm patients. Mirror aneurysms showed a predilection for the cavernous carotid artery, whereas they were comparatively rare in the posterior circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
1
14
0
2
Order By: Relevance
“…A previous study indicated that the characteristics or natural history of IAs in patients with multiple aneurysms might be different from those with a single IA. 40 For instance, it was reported that posterior circulation aneurysms were less frequent in patients with multiple IAs than in patients with a single aneurysm, which we also observed in our study (only 3% of IAs were located at the posterior circulation). Moreover, previous models were trained to discriminate ruptured cohorts from unruptured cohorts without associating the coexisting IAs within each patient.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study indicated that the characteristics or natural history of IAs in patients with multiple aneurysms might be different from those with a single IA. 40 For instance, it was reported that posterior circulation aneurysms were less frequent in patients with multiple IAs than in patients with a single aneurysm, which we also observed in our study (only 3% of IAs were located at the posterior circulation). Moreover, previous models were trained to discriminate ruptured cohorts from unruptured cohorts without associating the coexisting IAs within each patient.…”
Section: Discussionsupporting
confidence: 87%
“…We also agree with the conclusions made by Lee et al in their study of over 200 mirror-like IAs. 22 They showed that the frequency of mirror-like IAs varies depending on the location, with mirror-like IAs being overrepresented among intracavernous IAs, for example. It suggests that different pathophysiological mechanisms may be at the root of the different aneurysm locations.…”
Section: Discussionmentioning
confidence: 99%
“…Mirror intracranial aneurysms occur in 2–12% of all patients with intracranial aneurysms ( 11 12 14 16 ). Despite their frequency of occurrence, they are not well studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they reported middle cerebral artery (MCA) as the most common site of mirror aneurysms, followed by a non-cavernous internal carotid artery (ICA), posterior communicating artery (PcomA), and cavernous ICA. However, the findings of Lee et al ( 12 ) were controversial. As per the study, there existed a difference of opinion regarding female predisposition and a family history of intracranial aneurysm and cited to be similar to non-mirror aneurysms; and a predilection shown for cavernous ICA was contrary to the results of Meissner et al ( 11 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation